Role of determination of mutation D112G in the diagnosis of patients with syndrome of biologically inactive growth hormone among children in Ukraine - Sprinchuk, N.A.; Dosenko, V. E. (Reports of the National Academy of Sciences of Ukraine, 2016)
The mutation D112G in a body height hormone gene at 50 children of Ukraine before sexual development's age, to whom the diagnosis of biologically inactive hormone of body height is made, is studied. This mutation is not found. To confirm the genetic syndrome biologically inactive GH, the sequencing of the growth hormone gene is recommended. The diagnosis of this syndrome should be guided by certain clinical and laboratory parameters.